VD_FINDINFO Arrêt / 2023 / 53 vom 23. Januar 2023 - VD Tribunal cantonal (2023)
VIRUSMALADIE, APG, SOCIÉTÉ ANONYME, SITUATION JURIDIQUE | 8 al. 1 Cst., 9 Cst., 12 LPGA, 2 al. 3 OAPG (COVID-19), 2 al. 3bis OAPG (COVID-19), 2 al. 3ter OAPG (COVID-19), 5 al. 2quater OAPG (COVID-19), 15 Loi COVID-19